Junctional adhesion molecules JAM-B and JAM-C promote autoimmune-mediated liver fibrosis in mice. (July 2018) - Hintermann, Edith; Bayer, Monika; Conti, Clara Benedetta; Fuchs, Sina; Fausther, Michel; Leung, Patrick S.; Aurrand-Lions, Michel; Taubert, Richard; Pfeilschifter, Josef M.; Friedrich-Rust, Mireen; Schuppan, Detlef; Dranoff, Jonathan A.; et al.
Abstract: Fibrosis remains a serious health concern in patients with chronic liver disease. We recently reported that chemically induced chronic murine liver injury triggers increased expression of junctional adhesion molecules (JAMs) JAM-B and JAM-C by endothelial cells and de novo synthesis of JAM-C by hepatic stellate cells (HSCs). Here, we demonstrate that biopsies of patients suffering from primary biliary cholangitis (PBC), primary sclerosing cholangitis (PSC) or autoimmune hepatitis (AIH) display elevated levels of JAM-C on portal fibroblasts (PFs), HSCs, endothelial cells and cholangiocytes, whereas smooth muscle cells expressed JAM-C constitutively. Therefore, localization and function of JAM-B and JAM-C were investigated in three mouse models of autoimmune-driven liver inflammation. A PBC-like disease was induced by immunization with 2-octynoic acid-BSA conjugate, which resulted in the upregulation of both JAMs in fibrotic portal triads. Analysis of a murine model of PSC revealed a role of JAM-C in PF cell-cell adhesion and contractility. In mice suffering from AIH, endothelial cells increased JAM-B level and HSCs and capsular fibroblasts became JAM-C-positive. Most importantly, AIH-mediated liver fibrosis was reduced in JAM-B −/− mice or when JAM-C was blocked by soluble recombinant JAM-C. Interestingly, loss of JAM-B/JAM-C function had no effect on leukocyte infiltration, suggesting that the well-documented function of JAMs in leukocyte recruitment to inflamed tissue was not effective in the tested chronic models. This might be different in patients and may even be complicated by the fact that human leukocytes express JAM-C. Our findings delineate JAM-C as a mediator of myofibroblast-operated contraction of the liver capsule, intrahepatic vasoconstriction and bile duct stricture. Due to its potential to interact heterophilically with endothelial JAM-B, JAM-C supports also HSC/PF mural cell function. Together, these properties allow JAM-B and JAM-C to actively participate in vascular remodeling associated with liver/biliary fibrosis and suggest them as valuable targets for anti-fibrosis therapies. Graphical abstract: Highlights: Junctional adhesion molecule JAM-C mediates hepatic myofibroblast contractility. Autoimmune-driven chronic liver inflammation triggers enhanced JAM-C expression. Blockade of JAM-C by soluble recombinant JAM-C prevents liver fibrosis in the mouse. Leukocyte immigration into inflamed tissue is not affected by JAM-C inhibition. JAM-C expression is found in liver biopsies of AIH, PBC, and PSC patients.